A study to assess the effectiveness of structured teaching programme on knowledge regarding selected prenatal diagnosis tests among staff nurses in selected hospital. - Ms. Manjusha Mahakarkar, Ms. Shalini H. Moon, Ms. Suvarna Ghugare (Drugs and Cell Therapies in Hematology, 2021)
Need of study: Congenital abnormalities caused around 260,000 neonatal deaths globally in 2011, according to World Health Statistics. 6 Genetic disorders have a major impact on people all over the world. Every year, half a million children in India are born with congenital malformations, the majority of which are caused by chromosomal abnormalities. Per year, about 9000 babies are born with thalasemia, 5200 with sickle cell disease, and 21000 with down syndrome. (Karagkiouzis,2015).Objectives of the study: 1.Using a standardised awareness questionnaire, measure staff nurses’ knowledge of chosen prenatal diagnostic examinations. 2.Using the same framework information questionnaire, determine the efficacy of a standardised teaching programme on knowledge of chosen prenatal diagnostic assessments by staff nurses.3.To see whether there’s a connection between pre-test awareness scores and demographic factors like age, schooling, practise location, expertise, and prior knowledge.Methodology: A pre-experimental one-group pretest-post-test template from AVBR Hospital was used in this sample, and 60 registered staff nurses were chosen by non-probability convenient sampling. Result: A pre-experimental research conducted in AVBR Hospital with 60 staff nurses to see the impact of teaching on foetal welfare using a non-probability easy sampling approach revealed that the mean pre-test knowledge was 42.3 percent and post-test knowledge was 78.3 percent. This demonstrates how coaching can assist staff nurses with learning about pregnancy diagnostic tests.